2020
DOI: 10.1007/s00268-020-05408-2
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy for Primary Aldosteronism: Significant Variability in Work‐Up Strategies and Low Guideline Adherence in Worldwide Daily Clinical Practice

Abstract: Background Various diagnostic tests are available to establish the primary aldosteronism (PA) diagnosis and to determine the disease laterality. Combined with the controversies in the literature, unawareness of guidelines and technical demands and high costs of some of these diagnostics, this could lead to significant differences in work-up strategies worldwide. Therefore, we investigated the work-up before surgery for PA in daily clinical practice within a multicenter study. Methods Patients who underwent uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
(80 reference statements)
0
10
1
Order By: Relevance
“…The median duration of hypertension was 96 [36–144] months. The median DDD was 3.7 [2.0–5.6] and median nodule size at imaging was 15 [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ] mm. In 7.9% of patients the nodule size was based on MRI, because no CT was performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median duration of hypertension was 96 [36–144] months. The median DDD was 3.7 [2.0–5.6] and median nodule size at imaging was 15 [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ] mm. In 7.9% of patients the nodule size was based on MRI, because no CT was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the worldwide increase in primary hypertension over the last decades could also have influenced the lower rates of complete clinical success within our study [ 23 ]. Since our cohort represents daily clinical practice, the preoperative workup within our cohort was less stringent in following current guidelines compared to the preselected PASO cohort [ 17 ]. This is especially seen in the difference in the routine performance of AVS, 100% in the PASO cohort versus 63.4% in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33,34 Furthermore, the use of AVS in daily clinical practice shows significant variability in expert centers. 35 Moreover, all studies primarily reported data on group level and we did not actively contact authors for individual patient data, which is expected to be favorable with considerable advantages (e.g. subgroup analysis or adjustment for confounding factors), over group level data.…”
Section: Discussionmentioning
confidence: 99%